2020
DOI: 10.1101/2020.11.17.386250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thiol-ene cross-linked alginate hydrogel encapsulation modulates the extracellular matrix of kidney organoids by reducing abnormal type 1a1 collagen deposition

Abstract: Differentiated kidney organoids from induced pluripotent stem cells hold promise as a treatment for patients with kidney diseases. Before these organoids can be translated to the clinic, shortcomings regarding their cellular, extracellular compositions and developmental plateau needs to be overcome. We performed a proteomic analysis on kidney organoids cultured for a prolonged culture time and we found a specific change in the extracellular matrix composition with increased expression of types 1a1, 2 and 6a1 c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 54 publications
2
18
0
Order By: Relevance
“…The 3D configurations and the role of mechanical as well as extracellular matrix (ECM) cues that influence cellular (de)differentiation to develop accurate organoid models need to be addressed in order to establish improved glomerular models in vitro . The effect of ECM cues and material stiffness on organoid differentiation was nicely shown by Garetta et al and also by Geuens and co-workers (Garreta et al, 2019; Geuens et al, 2021). Organoids encapsulated in soft biomaterials showed accelerated differentiation, less fibrosis upon aging, and reduced off-target cell populations, all aspects that will aid in signaling to enhance the maturation of podocytes but also other kidney segments like the proximal tubule and the collecting duct.…”
Section: Discussionsupporting
confidence: 55%
“…The 3D configurations and the role of mechanical as well as extracellular matrix (ECM) cues that influence cellular (de)differentiation to develop accurate organoid models need to be addressed in order to establish improved glomerular models in vitro . The effect of ECM cues and material stiffness on organoid differentiation was nicely shown by Garetta et al and also by Geuens and co-workers (Garreta et al, 2019; Geuens et al, 2021). Organoids encapsulated in soft biomaterials showed accelerated differentiation, less fibrosis upon aging, and reduced off-target cell populations, all aspects that will aid in signaling to enhance the maturation of podocytes but also other kidney segments like the proximal tubule and the collecting duct.…”
Section: Discussionsupporting
confidence: 55%
“…Next, we simulated a 9-fold change [which was the maximum fold-change observed in kidney organoid ECM mass spectrometry experiments by Geuens et al (2020a) ] between days 18 and 25 ( Figure 2 condition 4) for L 2. This simulation was done to reflect the effect of a higher fold of the ligand with the lower integrin binding rate on the system.…”
Section: Resultsmentioning
confidence: 99%
“…Using the ODE system described above, we performed a set of in silico experiments, aimed at characterizing the effects of increased ECM ligand concentration on integrin binding in a cell culture system. Initial molar concentrations for fibronectin (0.18 nM) and vWA (0.33 nM) were taken from Hudson et al while we used the fold changes reported by Geuens et al (2020a) between days 18 and 25 for these two ligands (2.5-fold and 1.5-fold for fibronectin and vWA) in kidney organoid culture. This way we obtained the test condition 1 “Different Initial Conditions, Different Fold Change” in Table 2 and Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations